Rotational flap versus long plantar flap for transmetatarsal amputation closure following revascularization - Vanessa Prado dos Santos, MD, PhD; Lucas de Mello Ferreira, MD; André Brito Queiroz, MD, PhD; Carlos Alberto Silveira Alves, MD (Journal of Vascular Surgery Cases and Innovative Techniques)
Objective: The integrity of the plantar flap is important for transmetatarsal amputation (TMA) classic closure. However, in ischemic wounds, the plantar flap can be compromised, making the TMA coverage difficult. The aim of this study was to compare the outcomes of rotational vs long plantar flaps for transmetatarsal amputation closure in patients with dysvascular partial foot amputations. Methods: We conducted an observational study including revascularized patients with established forefoot gangrene who required TMA. The coverage was performed by classical long plantar flap or rotational flap due to the lack of adequate plantar skin. Seventeen patients were included in the study. TMA was performed after lower limb revascularization in all cases. We compared the wound healing and functional outcomes of the two groups (rotational vs long plantar flap). Results: The mean age of the sample was 66.5 years (±8.3 years). Eight cases (47%) had open surgical bypass, and nine (53%) had endovascular procedures. Eight cases of rotational flaps (7 medial plantar rotational flaps) and nine classical long plantar flaps were analyzed. Our results demonstrated an overall healing rate of 77% in the sample. There was no significant difference between the surgical techniques evaluated. The healing percentage for the rotational flap group was 75% (6 cases) and 78% (7 cases) for the classical long plantar flap closure (P = .6). Conclusions: Rotational flap provides a feasible alternative to classical long plantar flap for TMA coverage, showing a satisfactory healing rate for dysvascular foot following revascularization.